Green Tourism and Tri Hita Karana Implementation at Suranadi Narmada Area, Lombok - Ahmad (Catuspata Press, 2021)
Abstract: Purpose: This research is to find out the development of green tourism through Tri Hita Karana in Suranadi Narmada Area, Lombok, West Nusa Tenggara, Indonesia. Research methods: Data collection was carried out by distributing questionnaires via Google form to 150 respondents. The research uses multiple linear regression analysis (multiple regression), classical assumption test, T test, F test, and determination coefficient test (R2). Findings: Parhyangan has a positive and significant effect on Suranadi Narmada Area. Pawongan has a positive and significant effect on Suranadi Narmada Area. Palemahan has a positive and significant effect on Suranadi Narmada Area. Tri Hita Karana (parhyangan, pawongan, palemahan) has a positive and significant effect on the tourist area of Suranadi Narmada. Implication: Tourism managers today are to pay more attention to tourism business which has ecological, economic, and social sustainability with a basis of local knowledge in such a green tourism paradigm.